Development of an Educational Game Tool, "Magic Spinman," to improve the Fine Motor Skills of Early Childhood Education Students - Fatmawati, Nilal Muna; Ardhita, Erni; Aini, Lutfia Nur; Zakariyya, Muhammad Adib; Sundari, Rista; Anggraini, Wardah (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2023)
One of the things that affects learning is the teacher's strategy. Therefore, there is a need for the proper method to use educational game tools that support learning activities. From the six aspects that will be stimulated, there is an imbalance in that, not many teachers provide sufficient proportion to all elements, one of them physical motor aspects (fine motor and gross motor). This research focuses on the development of educational games aimed at increasing fine motor development in early childhood through educational games, which is provided in introducing knowledge of various objects around. The method used is research and development (Research & Development) with data collection techniques through interviews, observation, and documentation. The subjects in this study were children aged 4-5 years in group A at TK Annur Semarang. The results of this study were 23 children who had practiced the educational game "Magic Spinman" properly and smoothly; from the pre-test and post-test activities, it was found that there was an increase from 17.5 to 22.4, so the average score achieved several 4.9. In addition, product trials were not only able to stimulate fine motor aspects but found several aspects of development, including aspects of religious, moral, cognitive, language, social-emotional, and artistic values in early childhood. So that the existence of "Magic Spinman" media can be useful in optimizing children's potential, being able to improve fine motor skills in early childhood, and being able to become a child's attraction and interest in learning through attractive designs.